An acid-responsive cascade drug release anti-tumor composite hydrogel delivery system and a preparation method and application thereof

CN122998056APending Publication Date: 2026-10-30ZHIYUAN BAIMAI (ZHEJIANG) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611498296.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本申请针对现有直接水凝胶载药体系中,小分子免疫调节剂和活性离子容易经水凝胶孔道提前扩散;另一方面,将纳米载体简单物理分散于水凝胶中时,纳米颗粒与水凝胶网络之间缺乏稳定的界面作用,难以同时兼顾颗粒局部固定、凝胶结构稳定和受控释放的问题,提供一种酸响应级联释药的抗肿瘤复合水凝胶递送系统,以解决相关技术中水凝胶递送体系存在的药物突释过快、力学性能差难以稳定等问题

Benefits of technology

[0019]进一步地,包括所述复合水凝胶在制备用于脉冲电场消融后肿瘤床局部递送材料、局部缓释抗肿瘤材料或残余肿瘤治疗辅助材料中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998056A_ABST
    Figure CN122998056A_ABST
Patent Text Reader

Abstract

The application discloses an acid-responsive cascade drug release antitumor composite hydrogel delivery system. The system comprises a dynamic cross-linked NDGA-chitosan hydrogel network and ZnS@PDA-R848 nanoparticles uniformly dispersed in the network. The ZnS@PDA-R848 is uniformly embedded in the NDGA hydrogel network through a PDA interface layer, so that the composite hydrogel has higher viscoelastic strength and more stable self-repairing recovery than the pure NDGA hydrogel, and the shear thinning injectability is maintained. The composite hydrogel realizes the programmed sustained release of NDGA, Zn 2+ H2S and R848 in the tumor local area through a multi-stage cascade process of "acid-responsive hydrogel network dissociation-nanoparticle local release-ZnS@PDA-R848 secondary acid-responsive drug release". The application can reduce the early diffusion of small molecule immunomodulators and active ions, prolong the local retention and action time, and is suitable for local delivery after nanosecond pulse electric field ablation of the tumor bed, and is used for inhibiting tumor growth and metastasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bio-hydrogel materials, and particularly relates to an acid-responsive cascade drug delivery system for antitumor composite hydrogels, its preparation method, and its application. Background Technology

[0002] Cancer treatment remains a pressing clinical challenge. Currently, surgical resection, radiotherapy, chemotherapy, and local ablation are widely used in clinical cancer treatment, but problems persist, including insufficient local drug retention, inadequate treatment area coverage, and incomplete removal of residual tumor cells. Traditional systemic drug delivery methods often result in insufficient drug accumulation at the tumor site and may cause toxic side effects to normal tissues. Therefore, developing material systems capable of local retention and sustained release of therapeutic components at the tumor site, while enhancing anti-tumor effects, is of great significance for improving the treatment efficacy of solid tumors.

[0003] Hydrogel materials possess excellent injectability, tissue conformability, local retention, and drug sustained-release capabilities, making them an important delivery platform for local tumor therapy. The tumor microenvironment is typically weakly acidic, a characteristic that can serve as an endogenous stimulus signal triggering hydrogel degradation and drug release. Nordihydroguaiac acid (NDGA), with its polyphenolic structure, can form dynamic borate ester bonds with crosslinked molecules containing boric acid groups, and further form a dynamic crosslinked network with amino-containing polymers. ZnS nanoparticles can release Zn under acidic conditions. 2+ H2S and R848 can be loaded into nanoparticles as functional therapeutic components.

[0004] While direct hydrogel loading can achieve high nominal drug loading, small molecule immunomodulators such as R848 and Zn... 2+ Active ions and H2S-related components tend to diffuse prematurely through the pores of hydrogels, resulting in significant problems of early burst release and excessively rapid local diffusion, making it difficult to meet the requirements for long-term sustained release after ablation. Therefore, existing materials for local tumor treatment still need further improvement. A novel composite hydrogel system needs to be developed that combines shear-thinning injectability, gel structure stability, microenvironment-responsive drug release, local fixation, and compatibility with local ablation therapies such as nanosecond pulsed electric fields to improve tumor treatment efficacy. Summary of the Invention

[0005] This application addresses the problems in existing direct hydrogel drug delivery systems, such as the tendency for small molecule immunomodulators and active ions to diffuse prematurely through the hydrogel channels; and the lack of stable interfacial interaction between nanoparticles and the hydrogel network when nanocarriers are simply physically dispersed in the hydrogel, making it difficult to simultaneously achieve local particle fixation, gel structure stability, and controlled release. This application provides an acid-responsive cascade drug release antitumor composite hydrogel delivery system to solve the problems of excessively rapid drug release and poor mechanical properties in hydrogel delivery systems of related technologies.

[0006] This invention constructs an acid-responsive cascade drug-release antitumor composite hydrogel based on acid-responsive hydrogels and acid-responsive nanoparticles. The stability of the composite hydrogel is enhanced by the interaction between the nanoparticle shell and the hydrogel crosslinking agent, creating a local drug reservoir and avoiding systemic drug circulation. Simultaneously, the acidic tumor microenvironment is utilized to dissociate the gel matrix and nanoparticles, enabling cascade drug release and ultimately achieving sustained co-delivery of antitumor functional factors. This composite hydrogel can reduce early leakage in a neutral environment and trigger enhanced release in the acidic tumor microenvironment.

[0007] One of the technical solutions of the present invention is to provide an antitumor composite hydrogel of acid-responsive cascade drug release.

[0008] The composite hydrogel is composed of NDGA-carboxymethyl chitosan hydrogel and ZnS@PDA-R848 nanoparticles; the NDGA-carboxymethyl chitosan hydrogel is formed by dynamic crosslinking of carboxymethyl chitosan solution and NDGA-derived crosslinking agent solution, and the ZnS@PDA-R848 nanoparticles are made by coating a PDA (polydopamine) shell with ZnS nanoparticles as the core and adsorbing R848 drug.

[0009] The polydopamine layer interacts with the NDGA-derived crosslinking agent through hydrogen bonds and π-π interactions, allowing the ZnS@PDA-R848 nanoparticles to be embedded in the dynamically crosslinked hydrogel network; this can improve the dispersion uniformity, interfacial compatibility, and local retention stability of the ZnS@PDA-R848 nanoparticles in the hydrogel network.

[0010] Under acidic conditions, the dynamically cross-linked hydrogel network dissociates and releases NDGA, exposing and / or releasing the ZnS@PDA-R848 nanoparticles; subsequently, the ZnS nanonuclei decompose to release Zn. 2+ It reacts with H2S and causes R848 to be released from the polydopamine layer, thereby forming an acid-responsive cascade release drug.

[0011] This composite hydrogel exhibits shear-thinning properties, allowing for local injection into the tumor lesion or the tumor bed after ablation using a syringe. After injection, it is fixed to the tissue, forming a local drug reservoir. The composite hydrogel tightly embeds ZnS@PDA-R848 within the hydrogel through hydrogen bonds and π-π bonds between PDA and NDGA, preventing particle loss through the hydrogel channels. Simultaneously, it acts as an anchoring point, enhancing the mechanical properties of the gel matrix and improving gel stability. Furthermore, this composite hydrogel can achieve a multi-stage cascade process in the specific acidic tumor microenvironment: "acid-responsive hydrogel network dissociation—local release of nanoparticles—secondary acid-responsive drug release of ZnS@PDA-R848." First, under neutral conditions, the dynamic network maintains local particle fixation; under acidic conditions, the borate ester bond / Schiff base dynamic network dissociates, releasing NDGA and exposing or releasing the nanoparticles. Second, after particle exposure, ZnS decomposes under acidic conditions, releasing Zn. 2+ And H2S, while R848 is released from the PDA layer. The technical effect of this system is not only to simultaneously deliver NDGA and Zn 2+ Instead of H2S and R848, the release of different therapeutic components is continuously controlled through two levels: hydrogel network and nanoparticles.

[0012] Through NDGA, Zn 2+ The programmed and sustained release of H2S and R848 at the tumor site achieves the combined delivery of four therapeutic factors: small molecule drugs, active metal ions, therapeutic gas molecules, and immunomodulators.

[0013] This application does not involve directly physically incorporating ZnS@PDA-R848 nanoparticles into the hydrogel as a conventional drug carrier. The PDA layer serves two purposes: firstly, as the loading interface for R848, and secondly, as an interface adaptation layer between ZnS@PDA-R848 and the NDGA dynamic hydrogel network. Through hydrogen bonding and π-π interactions between PDA and NDGA, the nanoparticles are stably embedded within the hydrogel network. Thus, the PDA layer simultaneously participates in nanodrug loading and the construction of the composite hydrogel interface.

[0014] The second technical solution of the present invention provides a method for preparing an acid-responsive cascade drug-releasing antitumor composite hydrogel, comprising: (1) Nodedihydroguaiac acid (NDGA) and 4-formylphenylboronic acid (FB) are reacted in an organic solvent to obtain an NDGA-derived crosslinker (RN-crosslinker); wherein the molar ratio of NDGA to FB is 1:(1-2), the organic solvent includes one or more of ethyl acetate, ethanol, and dimethylformamide, the reaction temperature is 40-75 °C, and the reaction time is 18-48 h.

[0015] (2) Dissolve carboxymethyl chitosan (C-CS) in water or buffer at a mass fraction of 3-5 wt% to obtain C-CS solution; dissolve or disperse RN-crosslinker in PBS buffer at a mass fraction of 4-10 mg / mL to obtain RN-crosslinker solution.

[0016] (3) Dissolve zinc salt, sulfur source and stabilizer in water and prepare ZnS nanoparticles by hydrothermal reaction; react ZnS nanoparticles with dopamine hydrochloride in alkaline buffer, and obtain ZnS@PDA nanoparticles after centrifugation and washing; further mix and incubate ZnS@PDA nanoparticles with R848 in ethanol solution, and obtain ZnS@PDA-R848 nanoparticles after centrifugation and washing; the zinc salt includes zinc acetate, zinc chloride or zinc nitrate; the sulfur source includes thiourea, sodium sulfide or thioacetamide; the stabilizer includes polyvinylpyrrolidone.

[0017] (4) ZnS@PDA-R848 nanoparticles were dispersed in an NDGA-derived crosslinking agent solution, allowing the polydopamine layer on the surface of the ZnS@PDA-R848 nanoparticles to undergo hydrogen bonding and π-π interactions with the NDGA-derived crosslinking agent; subsequently, a carboxymethyl chitosan solution was added, and the composite hydrogel was formed through dynamic crosslinking via borate ester bonds and Schiff base bonds. The volume ratio of the C-CS solution to the NDGA-derived crosslinking agent solution was 1:1; the ZnS@PDA-R848 nanoparticles accounted for 1-10% of the total solution mass.

[0018] The third technical solution of this invention provides an application of the acid-responsive cascade drug-releasing antitumor composite hydrogel prepared by the above method. This includes its application in the preparation of drugs or medical materials for antitumor treatment, wherein the antitumor treatment includes local treatment of liver cancer, postoperative tumor treatment, and treatment of residual tumor after tumor ablation.

[0019] Furthermore, this includes the application of the composite hydrogel in the preparation of materials for local delivery to the tumor bed after pulsed electric field ablation, locally sustained-release antitumor materials, or adjuvant materials for the treatment of residual tumors.

[0020] The advantages of this invention are as follows: The NDGA composite hydrogel designed in this invention possesses injectability, tissue adhesion, shear-thinning properties, self-healing ability, pH-responsive degradation, and multi-component release performance. Compared with simple nanoparticle drug delivery, the hydrogel network acts as a local reservoir, prolonging the retention time of nanoparticles in the tumor bed. In vitro performance testing demonstrates that, compared with the simple hydrogel system, the introduction of ZnS@PDA-R848 nanoparticles not only improves the viscoelastic strength and structural stability of the composite hydrogel through particle-network interface interactions, but also significantly inhibits the early burst release of R848 and Zn²⁺ under physiological conditions through a dual acid-responsive gating mechanism of physical confinement of the hydrogel network and chemical encapsulation of nanoparticles. Animal experiments demonstrate that the composite hydrogel exhibits stable retention at the tumor site, improves systemic safety during treatment, prolongs the action time of local therapeutic components, and has good anti-tumor effects.

[0021] The preparation method of this invention is simple, and the acid-responsive cascade drug release antitumor composite hydrogel delivery system has stable performance and broad application prospects. Attached Figure Description

[0022] Figure 1 This is a structural characterization diagram of the RN-crosslinker in Example 1. Figure 1 In this diagram, 'a' represents the hydrogen nuclear magnetic resonance spectrum. Figure 1 In this diagram, b represents the Fourier transform infrared spectrum. Figure 2 These are morphological and structural characterization images of the ZnS nanoparticles in Example 1. Figure 2 In the image, 'a' represents a transmission electron microscope (TEM) image. Figure 2 In the diagram, 'b' represents the element distribution map; Figure 3 Characterization of the ZnS@PDA-R848 nanoparticles in Example 1; Figure 3 In the image, 'a' represents a transmission electron microscope (TEM) image of ZnS@PDA-R848 nanoparticles. Figure 3 In the diagram, b represents the particle size distribution of ZnS, ZnS@PDA, and ZnS@PDA-R848 nanoparticles. Figure 3 In the diagram, 'c' represents the zeta potential of ZnS, ZnS@PDA, and ZnS@PDA-R848 nanoparticles. Figure 3 In the figure, d represents the UV absorption spectra of R848, ZnS@PDA, and ZnS@PDA-R848 nanoparticles; Figure 4 The image shows a scanning electron microscope (SEM) image and elemental distribution map of the NDGA composite hydrogel in Example 1. Figure 5The figures show the tissue adhesion, injectability, rheological properties, and self-healing properties of different hydrogels, such as NZPR@Gel in Example 1, N@Gel in Comparative Example 1, and NZ@Gel in Comparative Example 2. Figure 5 In the image, 'a' represents a physical illustration of the tissue adhesion properties of NZPR@Gel. Figure 5 In the image, b represents an injectable sample of NZPR@Gel. Figure 5 c in the figure represents the viscosity-shear rate curves of NZPR@Gel, N@Gel, and NZ@Gel. Figure 5 In the figure, d represents the frequency scanning curve of NZPR@Gel and N@Gel, NZ@Gel. In the figure, G′ represents the energy storage modulus and G″ represents the loss modulus. Figure 5 In the figure, e, f, and g are the self-healing rheological curves of N@Gel, NZ@Gel, and NZP@Gel under alternating high and low strains, respectively. Figure 5 In the diagram, 'h' represents a physical image of the self-healing behavior of the gels prepared in Examples 1 and 2. Figure 6 The graph shows the degradation performance of the NZPR@Gel composite hydrogel in Example 1 under different pH conditions. Figure 7 The graph shows the NDGA release performance of the NZPR@Gel composite hydrogel under different pH conditions in Example 4 of this invention. Figure 8 Zn in the NZPR@Gel composite hydrogel under different pH conditions in Example 5 of this invention. 2+ Release, H2S release, and R848 release performance diagrams; Figure 9 The NZPR@Gel composite hydrogel, ZnS nanoparticles in Example 6 of this invention, and the NZ@Gel composite hydrogel in Comparative Example 2 are compared under different pH conditions. 2+ Release performance graph; Figure 10 This is a diagram illustrating the in vitro killing effect of the NZPR@Gel composite hydrogel on tumor cells in Example 7 of this invention. Figure 11 This is a diagram illustrating the in vivo antitumor effect of NZPR@Gel combined with nanosecond pulsed electric field in animals in Example 8 of this invention. Figure 11 In this context, 'a' refers to the hydrogel-ablation integrated device in Embodiment 8 of the present invention. Figure 11 In Example 8 of this invention, b represents the actual tumor images after treatment in the PBS group (Control), nanosecond pulsed electric field (nsPEF) group, Example 1 (NZPR@Gel) group, and nsPEF+NZPR@Gel group. Figure 11In the figure, 'c' represents the tumor inhibition rate graph corresponding to each of the above groups; Figure 12 This is a diagram illustrating the inhibitory effect of NZPR@Gel composite hydrogel on lung metastasis in a metastasis model in Example 9 of this invention. Figure 12 In the figure, 'a' represents actual images of lung tissue after treatment in the PBS group (Control), nanosecond pulsed electric field (nsPEF) group, Example 1 (NZPR@Gel) group, and nsPEF+NZPR@Gel group. Figure 12 In the figure, b represents the statistical chart of the number of lung metastatic tumors in each of the above groups; Figure 13 This is a diagram showing the local retention and degradation effects of the NZPR@Gel composite hydrogel in an animal in Example 10 of the present invention. Figure 14 This is a biosafety evaluation diagram of the NZPR@Gel composite hydrogel in Example 11 of the present invention. Detailed Implementation

[0023] The following examples are provided to further illustrate the present invention and are intended to explain the invention, not to limit its scope. Unless otherwise specified, all figures are expressed in parts by weight and weight percentages.

[0024] Unless otherwise specified, the raw materials used in this invention are all conventional commercially available products; unless otherwise specified, the methods used in this invention are all conventional methods in the field.

[0025] The embodiments of the present invention will be further described below with reference to several examples.

[0026] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.

[0027] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0028] Example 1 1. Preparation of RN-crosslinker: Step (1.1): Weigh 300 mg of NDGA and 297.5 mg of FB, and add them to a 100 mL round-bottom flask at a molar ratio of 1:2; Step (1.2): Add 15 mL of ethyl acetate to the round-bottom flask to disperse FB and NDGA in the reaction system; Step (1.3): The reaction system was placed in an oil bath at 75 °C and stirred for 18 h. During the reaction, a white precipitate was gradually formed. Step (1.4): After the reaction is complete, centrifuge the reaction solution, discard the supernatant, and collect the precipitate; In step (1.5), the precipitate was washed twice with ethyl acetate and then dried at 60 °C for 6 h to obtain a white powdery RN-crosslinker with a yield of 65.7%.

[0029] The phenolic hydroxyl groups in NDGA react with the boric acid groups in FB to form a borate ester structure. At the same time, the aldehyde groups in FB can provide reaction sites for subsequent Schiff base dynamic crosslinking with the amino groups in carboxymethyl chitosan.

[0030] 2. Preparation of ZnS nanoparticles, including the following steps: Step (2.1): Weigh 0.2 g zinc acetate, 1.2 g PVP and 1.4 g thiourea, dissolve them in 20 mL deionized water to obtain a homogeneous solution; Step (2.2): Transfer the above solution to a polytetrafluoroethylene-lined reactor and react at 150 °C for 1 h. Step (2.3): After the reaction is complete, cool to room temperature, centrifuge the product at 12,000 rpm for 10 min, and collect the precipitate; Step (2.4): Wash the precipitate three times with deionized water to obtain ZnS nanoparticles.

[0031] The obtained ZnS nanoparticles can decompose and release Zn in an acidic environment. 2+ H2S, used to enhance the local treatment effect of tumors.

[0032] 3. Preparation of ZnS@PDA nanoparticles, including the following steps: Step (3.1): Weigh 30 mg of ZnS nanoparticles and 30 mg of dopamine hydrochloride and disperse them in 15 mL of Tris-HCl buffer. Step (3.2): The mixture is stirred and reacted under light-protected conditions for 24 h to allow dopamine to self-polymerize on the surface of ZnS nanoparticles to form a polydopamine coating layer; Step (3.3): After the reaction is complete, centrifuge at 12,000 rpm for 10 min and collect the precipitate; In step (3.4), the precipitate was washed three times with deionized water and three times with ethanol to obtain ZnS@PDA nanoparticles.

[0033] PDA coating can improve the stability of ZnS nanoparticles and provide a basis for subsequent surface chemical bonding of R848.

[0034] 4. Preparation of ZnS@PDA-R848 nanoparticles, including the following steps: Step (4.1): Disperse ZnS@PDA powder and R848 in ethanol; Step (4.2): The mixture was stirred and incubated for 24 h under light-protected conditions to load R848 into ZnS@PDA nanoparticles; Step (4.3): After the reaction is complete, centrifuge at 12,000 rpm for 10 min and collect the precipitate; In step (4.4), the precipitate was washed three times with ethanol and then three times with deionized water to obtain ZnS@PDA-R848 nanoparticles.

[0035] In this embodiment, R848 is loaded as a functional therapeutic component in ZnS@PDA nanoparticles, and the resulting ZnS@PDA-R848 nanoparticles can be further used to prepare NDGA composite hydrogels.

[0036] 5. Preparation of NDGA composite hydrogel NZPR@Gel, including the following steps: Step (5.1): ZnS@PDA-R848 nanoparticles were dispersed at a mass fraction of 10 wt% in an RN-crosslinker solution of 10 mg / mL to obtain an RN-crosslinker dispersion containing ZnS@PDA-R848. Step (5.2): Add an equal volume of 5 wt% carboxymethyl chitosan C-CS solution to the above dispersion; Step (5.3): After thorough mixing, allow the mixture to stand at 4 ℃ to form a gel, thus obtaining the NDGA composite hydrogel NZPR@Gel.

[0037] In this embodiment, ZnS@PDA-R848 nanoparticles are uniformly distributed within the NDGA hydrogel network. The polydopamine coating layer helps improve the interfacial compatibility between the ZnS@PDA-R848 nanoparticles and the NDGA hydrogel network, allowing the nanoparticles to be stably embedded in the hydrogel network, thereby forming a structure that combines acid-responsive degradation and ZnS@PDA-R848 hydrogel network properties. 2+ / H2S release and R848 delivery capabilities.

[0038] The prepared ZnS nanoparticles, ZnS@PDA nanoparticles, ZnS@PDA-R848 nanoparticles and NDGA composite hydrogel were dried respectively. The microstructure of the hydrogel was observed using a scanning electron microscope. The morphology of ZnS nanoparticles, ZnS@PDA nanoparticles and ZnS@PDA-R848 nanoparticles was observed using transmission electron microscopy. Elemental distribution analysis was used to observe the distribution of elements such as Zn, S, C, N, and O in nanoparticles or composite hydrogels; The structure and physicochemical properties of nanoparticles and composite hydrogels were characterized by X-ray diffraction, ultraviolet absorption spectroscopy, particle size and potential detection.

[0039] Figure 1 The structural characterization diagram of the RN-crosslinker demonstrates that NDGA reacts with FB to form an NDGA-derived crosslinking agent. Figure 1 From top to bottom, 'a' represents FB, NDGA, and NDGA-derived crosslinker (RN-crosslinker). Figure 2 The images show transmission electron microscopy (TEM) images and elemental distribution diagrams of ZnS nanoparticles. It can be seen that the ZnS nanoparticles have a uniform morphology and that Zn and S elements are evenly distributed. Figure 3 Characterization images of ZnS@PDA and ZnS@PDA-R848 nanoparticles demonstrate the success of polydopamine coating and R848 loading. Figure 4 The images show the scanning electron microscope (SEM) image and elemental distribution map of the NZPR@Gel composite hydrogel. It can be seen that the composite hydrogel has a porous network structure and contains elements such as Zn and S, proving that ZnS@PDA-R848 nanoparticles were successfully introduced into the hydrogel network.

[0040] Example 2 The differences from Example 1 are as follows: In step (1.1) of preparing the RN-crosslinker, 300 mg of NDGA and 148.5 mg of FB were weighed and added to a 100 mL round-bottom flask at a molar ratio of 1:1; in step (1.3), the reaction system was placed in an oil bath at 40 °C and stirred for 48 h; the yield was 76.1%. In step (5.1) of preparing the NDGA composite hydrogel NZPR@Gel, ZnS@PDA-R848 nanoparticles were dispersed at a mass fraction of 1 wt% in a 4 mg / mL RN-crosslinker solution to obtain an RN-crosslinker dispersion containing ZnS@PDA-R848; in step (5.2), the concentration of the carboxymethyl chitosan C-CS solution was 3 wt%. The rest was the same as in Example 1.

[0041] Comparative Example 1 The difference from Example 1 is that an NDGA composite hydrogel without ZnS@PDA nanoparticles and R848 drug was prepared, denoted as N@Gel. Everything else is the same as in Example 1.

[0042] Comparative Example 2 The difference from Example 1 is that an NDGA composite hydrogel containing ZnS nanoparticles was prepared, denoted as NZ@Gel. Everything else is the same as in Example 1.

[0043] Example 3 The NZPR@Gel composite hydrogel obtained in Example 1 was tested using a rotational rheometer, with N@Gel from Comparative Example 1 and NZ@Gel from Comparative Example 2 used as comparisons to compare the effects of ZnS particles and the PDA interface layer on the shear thinning properties, viscoelastic strength, and structural recovery performance of the NDGA hydrogel. In the shear thinning experiment, as the shear rate increased from the low shear region to the high shear region, the viscosity of both N@Gel and NZPR@Gel gradually decreased, indicating that both have shear thinning properties, facilitating local delivery via syringes, puncture needles, catheters, or hollow ablation electrodes. Among them, the overall viscosity of NZPR@Gel was higher than that of N@Gel and NZ@Gel at the same shear rate, indicating that the embedding of ZnS@PDA-R848 nanoparticles can enhance the hydrogel network structure. In the frequency scanning experiment, the storage modulus G′ of both hydrogels was higher than the loss modulus G″ within the test frequency range, indicating that the hydrogels were in a stable gel state. Specifically, G′ of NZPR@Gel was significantly higher than that of N@Gel, indicating that the introduction of PDA into the nanoparticles improved the viscoelastic strength of the hydrogel. In the strain scanning experiment, NZPR@Gel maintained a higher G′ and kept G′ higher than G″ in the low strain range. Under higher strain, the network was disrupted and exhibited a gel-sol transition. In the alternating high and low strain self-healing experiment, the hydrogel network was disrupted under high strain conditions. After recovering to low strain, G′ could rise again and be higher than G″ again, indicating that the dynamic borate ester bonds and Schiff base bonds endow the hydrogel with reversible reconstruction ability. Compared with N@Gel and NZ@Gel, it showed more stable modulus recovery in the cyclic test, indicating that the embedding of PDA is beneficial to improving the structural stability and post-injection recovery ability of the composite hydrogel.

[0044] Figure 5Characterization figures for the tissue adhesion, injectability, rheological properties, and self-healing properties of different hydrogels are shown. These include viscosity-shear rate curves, frequency scan curves, strain scan curves, and self-healing rheological curves under alternating high and low strain for N@Gel, NZ@Gel, and NZPR@Gel. These figures were used to evaluate the influence of the PDA interface layer and ZnS@PDA-R848 nanoparticles on the stability of the hydrogel network. As shown in the figures, the NDGA composite hydrogel can be extruded using a syringe and adheres to the tissue surface. Meanwhile, NZPR@Gel exhibits higher viscosity and storage modulus compared to N@Gel and NZ@Gel, and recovers its gel state after alternating strain failure, indicating that it possesses injectability, mechanical stability, and self-healing properties, making it suitable for local tumor drug delivery and tumor bed filling after ablation.

[0045] Example 4 An NDGA release test was performed on the NZPR@Gel composite hydrogel obtained in Example 1, including: Step (1): Add 250 μL of the freshly prepared NZPR@Gel hydrogel precursor solution from Example 1 to a 15 mL centrifuge tube to allow it to gel. Step (2): After gelation, add 5 mL of PBS solution with pH 7.4, 6.5 and 5.0 respectively; Step (3): Incubate the sample in a shaker at 37 ℃ and 50 rpm. Step (4): Take 200 μL of release medium at the predetermined time point and add an equal volume of fresh PBS corresponding to the pH. Step (5): The concentration of NDGA in the release solution was detected by high performance liquid chromatography.

[0046] Figure 6 The figure shows the degradation performance of the NZPR@Gel composite hydrogel under different pH conditions. As can be seen from the figure, the NDGA composite hydrogel maintains good structural stability at pH 7.4, while degradation accelerates at pH 6.5 and pH 5.0, indicating that the composite hydrogel exhibits acid-responsive degradation properties. Figure 7 The figure shows the NDGA release performance of the NDGA composite hydrogel under different pH conditions. As can be seen from the figure, the NDGA release rate and amount are higher under acidic conditions than under neutral conditions, indicating that the composite hydrogel can release therapeutic components in response to acidic environments.

[0047] Example 5 The NZPR@Gel composite hydrogel obtained in Example 1 was subjected to Zn treatment. 2+ H2S and R848 release performance tests, including: Step (1): The NZPR@Gel composite hydrogel was placed in PBS solutions with pH values ​​of 7.4, 6.5 and 5.0 and incubated with shaking at 37°C. Step (2): Samples are taken at predetermined time points to detect Zn in the release solution. 2+ concentration; Step (3): The amount of H2S released is detected by the methylene blue colorimetric method. Specifically, after sampling and centrifugation, the supernatant is mixed with the methylene blue colorimetric reagent and reacted in the dark for 30 min. The absorbance is measured at 665 nm and the amount of H2S released is calculated according to the Na2S standard curve. Step (4): Place NZPR@Gel in a dialysis bag with a molecular weight cutoff of 3500 Da and in PBS release media of different pH values, and incubate with shaking at 37 °C. Step (5): Take the external solution at the predetermined time point and add an equal volume of fresh PBS. Use ultraviolet absorption spectroscopy or standard curve to quantify the R848 content in the solution.

[0048] Figure 8 Zn in NZPR@Gel composite hydrogels under different pH conditions 2+ Release performance graphs of H2S and R848. As shown in the graphs, the NZPR@Gel composite hydrogel exhibits faster Zn release in acidic environments. 2+ The release behavior of H2S and R848 was observed, while the release was relatively low at pH 7.4, indicating that the composite hydrogel can reduce early leakage in a neutral environment and trigger enhanced release in the acidic tumor microenvironment.

[0049] Example 6 This embodiment provides Zn in individual nanoparticles and different NDGA composite hydrogels. 2+ The release behavior was compared with that of R848 to evaluate the effect of the PDA interface layer on the local fixation and early release of nanoparticles.

[0050] Step (1): Prepare ZnS nanoparticles in Example 1, NZPR@Gel in Example 1 and NZ@Gel in Comparative Example 2 respectively; Step (2): Place each group of materials in PBS release medium at pH 7.4 and pH 5.0 respectively, and incubate with shaking at 37 °C; Step (3): Take samples at predetermined time points and detect Zn in the release solution. 2+ and R848 content; Step (4): Compare the release behavior of different hydrogels under neutral and acidic conditions.

[0051] Figure 9Zn in different NDGA composite hydrogels 2+ A comparison of release behavior is shown in the figure. As can be seen, ZnS, NZ@Gel, and NZPR@Gel all exhibited relatively low release at pH 7.4, while release increased at the acidic pH 5.0. Specifically, compared to ZnS or NZ@Gel without a PDA interface layer, NZPR@Gel showed a slower initial release, indicating that the PDA interface layer effectively controls the sustained release of the therapeutic component and works in conjunction with the acid-responsive hydrogel network to achieve a cascade release.

[0052] Example 7 This embodiment provides verification of the anti-tumor effect of the NZPR@Gel composite hydrogel in Example 1 at the cellular level, including: Step (1): Seed tumor cells into a cell culture plate and culture them until they adhere to the plate; Step (2): Add different concentrations of NZPR@Gel to culture media at pH 7.4, pH 6.5 and pH 5.0 respectively for treatment; Step (3): After processing for a certain period of time, cell viability testing is used to evaluate the killing effect of different materials on tumor cells.

[0053] Figure 10 The figure shows the in vitro killing effect of NZPR@Gel on tumor cells. As can be seen from the figure, under neutral conditions (pH 7.4), NZPR@Gel showed no significant cytotoxicity; however, under acidic conditions (pH 6.5 and pH 5.0), the survival rate of tumor cells decreased continuously with increasing NZPR@Gel concentration, indicating that NZPR@Gel has a good acid-responsive tumor cell killing effect.

[0054] Example 8 This embodiment provides verification of the antitumor application of the NZPR@Gel composite hydrogel in Example 1 in animals, including: Step (1): Establish a mouse subcutaneous tumor model; Step (2): After the tumor grows to a certain size, the mice are randomly divided into PBS group, nanosecond pulsed electric field (nsPEF) group, NZPR@Gel group and nsPEF+NZPR@Gel group; Step (3): The PBS group was treated with PBS, the nsPEF group was treated with nanosecond pulsed electric field, the NZPR@Gel group was locally injected with NZPR@Gel, and the nsPEF+NZPR@Gel group was first treated with nanosecond pulsed electric field and then locally injected with NZPR@Gel. Step (4): Record the changes in tumor volume and body weight of mice in each group, and collect and weigh tumor tissue at the end of the experiment; Figure 11 The figures show the anti-tumor effects of the hydrogel-ablation integrated device and in animals. As can be seen from the figures, compared with the PBS group, both the nsPEF group and the NZPR@Gel group can inhibit tumor growth to a certain extent. The nsPEF+NZPR@Gel group shows a more significant tumor inhibition effect, indicating that the NZPR@Gel composite hydrogel can be used for local tumor treatment and can exert an anti-tumor effect in combination with nanosecond pulsed electric field ablation.

[0055] Example 9 This embodiment provides validation of the application of the NZPR@Gel composite hydrogel in Example 1 in inhibiting lung metastasis in a metastasis model, including: Step (1): Establish a mouse lung metastasis model; Step (2): Establish a subcutaneous tumor model associated with the lung metastasis model, and randomly divide mice into PBS group, nsPEF group, NZPR@Gel group and nsPEF+NZPR@Gel group; Step (3): Subcutaneous tumor sites are treated with PBS, nsPEF, or NZPR@Gel local injection, or nsPEF treatment combined with NZPR@Gel local injection. Step (4): Collect lung tissue at the end of the experiment, observe the appearance of the lung tissue, and count the number of metastatic nodules in the lung.

[0056] Figure 12 The figure shows the effect of NZPR@Gel composite hydrogel combined with nanosecond pulsed electric field on lung metastasis inhibition in a metastasis model. As can be seen from the figure, compared with the PBS group, both the nsPEF group and the NZPR@Gel group can reduce lung metastasis burden to some extent. The nsPEF+NZPR@Gel group shows a more significant lung metastasis inhibition effect, indicating that the NDGA composite hydrogel can also be used to reduce tumor metastasis-related burden in addition to local tumor treatment.

[0057] Example 10 This embodiment provides verification of the local retention and degradation performance of the NZPR@Gel composite hydrogel in animal vivo, including: Step (1): The freshly prepared NZPR@Gel composite hydrogel is injected locally into the subcutaneous tissue or target tissue of mice; Step (2): Sacrifice the mice at the predetermined time point, expose the drug administration site and observe the hydrogel residue; Step (3): Collect the residual hydrogel and weigh it to calculate the amount of residual hydrogel at different time points; Step (4): Based on the results of the change in hydrogel residue over time, evaluate the local retention and degradation performance of NZPR@Gel composite hydrogel in vivo.

[0058] Figure 13 This image shows the local retention and degradation effects of the NZPR@Gel composite hydrogel in animals. From left to right, the image represents three parallel experiments. As can be seen, the composite hydrogel can maintain local retention at the drug delivery site for a certain period and gradually degrades over time. This indicates that the composite hydrogel can act as a locally confined reservoir, prolonging the release and duration of action of therapeutic components in the drug delivery area.

[0059] Example 11 This embodiment provides a biosafety evaluation of the NZPR@Gel composite hydrogel, including: Step (1): Locally inject NZPR@Gel composite hydrogel into mice; Step (2): Seven days later, the main organs such as heart, liver, spleen, lungs and kidneys were collected, fixed, embedded, sectioned and stained with hematoxylin and eosin; Step (3) evaluate the in vivo biocompatibility of NZPR@Gel composite hydrogel based on histological results of major organs.

[0060] Figure 14 This is a biocompatibility evaluation diagram of the NZPR@Gel composite hydrogel. As shown in the diagram, the NZPR@Gel composite hydrogel did not cause significant tissue damage after administration, indicating that the composite hydrogel has good biocompatibility and safety for in vivo application.

[0061] The above embodiments describe in detail the structure, features, and effects of the present invention. The above description is only a preferred embodiment of the present invention. Any changes made in accordance with the concept of the present invention, or equivalent embodiments modified to have equivalent changes, shall still fall within the scope of protection of the present invention if they do not exceed the scope covered by the specification.

Claims

1. An acid-responsive cascade drug delivery system for antitumor composite hydrogels, characterized in that, include: The dynamic cross-linked hydrogel network is formed by cross-linking carboxymethyl chitosan with NDGA-derived cross-linking agents through borate ester bonds and Schiff base bonds. And ZnS@PDA-R848 nanoparticles dispersed in the hydrogel network, wherein the ZnS@PDA-R848 nanoparticles are composed of ZnS nanocores, polydopamine layers and loaded R848; the NDGA-derived crosslinking agent is obtained by crosslinking demethyldihydroguaiac acid with 4-formylphenylboronic acid; The polydopamine layer interacts with the NDGA-derived crosslinking agent through hydrogen bonds and π-π interactions, enabling the ZnS@PDA-R848 nanoparticles to be embedded in the dynamic crosslinked hydrogel network; Under acidic conditions, the dynamically cross-linked hydrogel network dissociates and releases NDGA, exposing and / or releasing the ZnS@PDA-R848 nanoparticles; subsequently, the ZnS nanonuclei decompose to release Zn. 2+ And H2S, and cause R848 to be released from the polydopamine layer.

2. A method for preparing an antitumor composite hydrogel of acid-responsive cascade drug release as described in claim 1, characterized in that, It includes the following steps: (1) The NDGA-derived crosslinking agent was obtained by reacting demethyldihydroguaiac acid with 4-formylphenylboronic acid in an organic solvent; (2) Dissolve carboxymethyl chitosan in water or buffer solution to obtain carboxymethyl chitosan solution; disperse the NDGA-derived crosslinking agent in water or buffer solution to obtain NDGA-derived crosslinking agent solution; (3) Dissolve zinc salt, sulfur source and stabilizer in water and prepare ZnS nanoparticles by hydrothermal reaction; react ZnS nanoparticles with dopamine hydrochloride in alkaline buffer to obtain ZnS@PDA nanoparticles; further mix ZnS@PDA nanoparticles with R848 and incubate to obtain ZnS@PDA-R848 nanoparticles. (4) Disperse ZnS@PDA-R848 nanoparticles in an NDGA-derived crosslinking agent solution, so that the polydopamine layer on the surface of the ZnS@PDA-R848 nanoparticles undergoes hydrogen bonding and π-π interaction with the NDGA-derived crosslinking agent; then add carboxymethyl chitosan solution, and form the composite hydrogel through dynamic crosslinking via borate ester bonds and Schiff base bonds.

3. The method according to claim 2, characterized in that, In step (1), the molar ratio of demethyldihydroguaiacol to 4-formylphenylboronic acid is 1:(1-2), the organic solvent includes one or more of ethyl acetate, ethanol, and dimethylformamide, the reaction temperature is 40-75 °C, and the reaction time is 18-48 h.

4. The method according to claim 2, characterized in that, In step (2), the mass fraction of the carboxymethyl chitosan solution is 3-5 wt%, and the concentration of the NDGA-derived crosslinking agent solution is 4-10 mg / mL.

5. The method according to claim 2, characterized in that, The zinc salt mentioned in step (3) includes zinc acetate, zinc chloride or zinc nitrate; the sulfur source includes thiourea, sodium sulfide or thioacetamide; and the stabilizer includes polyvinylpyrrolidone.

6. The method according to claim 2, characterized in that, In step (4), the volume ratio of carboxymethyl chitosan solution to NDGA-derived crosslinking agent solution is 1:1; ZnS@PDA-R848 nanoparticles account for 1-10 wt% of the total solution mass.

7. The application of an antitumor composite hydrogel delivery system for an acid-responsive cascaded release drug as described in claim 1.

8. The application according to claim 7, characterized in that, This includes applications in the preparation of antitumor drugs or medical materials.

9. The application according to claim 8, characterized in that, The antitumor composite hydrogel delivery system is used in the preparation of materials for local delivery to the tumor bed after pulsed electric field ablation, locally sustained-release antitumor materials, or adjuvant materials for the treatment of residual tumors.